The next day : transitions, change, and moving forward - Gates, Melinda, 1964- (New York : Flatiron Books, 2025)
"Melinda French Gates reflects on some of the most significant transitions in her own life, including becoming a parent, the death of a dear friend, and her departure from the Gates Foundation."--
Find Your Small Wave -- Feel the Ease of Letting Go -- Be a Greenhouse -- Distill Your Inner Voice -- Pause in the Clearing -- Plant Roots -- Emerge.
Keywords: Life change events; Self-realization.; Change (Psychology)